2015
DOI: 10.1111/hpb.12319
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic fistulae after pancreatic resections for neuroendocrine tumours compared with resections for other lesions

Abstract: High rates of POPF were found in patients operated for PNET. However, this was mainly owing to the fact that atypical resections, known to be associated with a higher fistula rate, were performed more frequently in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 51 publications
2
17
0
3
Order By: Relevance
“…Normal underlying pancreatic texture partly contributes to more frequent PF occurrence. In addition, common risk factors identified for EU associated with PF in other literature included: soft texture of remnant pancreas, MPD diameter less than 3 mm, distance between tumor and MPD, body mass index, New York Heart Association (NYHA) class II or III, operation time ≥180 min, certain inherited genetic diseases, and deep EU (Goasguen et al, 2009;Brient et al, 2012;Inchauste et al, 2012;Zhang et al, 2013;Heeger et al, 2014;Atema et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Normal underlying pancreatic texture partly contributes to more frequent PF occurrence. In addition, common risk factors identified for EU associated with PF in other literature included: soft texture of remnant pancreas, MPD diameter less than 3 mm, distance between tumor and MPD, body mass index, New York Heart Association (NYHA) class II or III, operation time ≥180 min, certain inherited genetic diseases, and deep EU (Goasguen et al, 2009;Brient et al, 2012;Inchauste et al, 2012;Zhang et al, 2013;Heeger et al, 2014;Atema et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы в специализированных клиниках летальность составляет около 5%, но частота осложнений остается высокой и может достигать 50% [1,2,17] [19]. Панкреатит в свою очередь приводит к таким осложнениям, как гастростаз, панкреатический свищ, аррозивное кровотечение [13][14][15]17].…”
Section: Discussionunclassified
“…Специфические осложнения (панкреатические свищи, гастростаз, аррозивное кровотечение) оценивали по классификации ISGPS [13][14][15].…”
Section: ближайший послеоперационный периодunclassified
“…Enucleation is often associated with higher POPF rates compared to other pancreatic surgeries (32), which could be in part due to the difficulty in suturing the pancreatic parenchyma together after enucleation (27). Haugvik et al (33) found that the overall rate of pancreatic fistula in their study of 72 patients who underwent laparoscopic enucleation was 50%, which was much higher than that for LDP (13.7%).…”
Section: Enucleationmentioning
confidence: 97%